Marine combined carbohydrates and inorganic ions in atmospheric total suspended particles across altitudes in the lower troposphere of Ny-Ålesund, Svalbard - Sebastian Zeppenfeld; Jonas Schaefer; Manuela van Pinxteren; Leon Schmidt (PANGAEA, 2025)
This dataset presents major aerosol particle constituents, including sodium, chloride, and combined carbohydrates, from balloon-borne samples collected in autumn 2021 and spring 2022 in Ny-Ålesund (Svalbard). Total suspended particle (TSP) samples were collected at altitudes ranging from 321 to 1112?m, encompassing both the boundary layer and the free troposphere. In addition, ground-based TSP samples were collected directly at the balloon winch site and at the Old Pier, where fresh sea spray aerosol (SSA) was sampled. Monosaccharides were quantified following acid hydrolysis of the combined carbohydrates.